Analytical solutions of the microscopic two-band theory for the temperature dependence of the upper critical fields of pure MgB₂ compared with experimental data - Palistrant, M.; Surdu, A.; Ursu, V.; Petrenko, P.; Sidorenko, A. (Физика низких температур, 2011)
Main theoretical results of the microscopic two-band theory for the temperature dependence of the upper critical fields H c₂(ab) and Hc₂(c) in pure two-band systems like MgB₂ are presented. The analytical solutions for the upper critical fields near the superconducting transition temperature and near the zero temperature were transformed to be directly compared with experimental data. The experimental Hc₂(ab) and Hc₂(c) temperature dependences of textured MgB2 films near the superconducting transition temperature were measured and compared with the respective theoretical formulas. The results of this theoretical approach were also compared with earlier published experimental data of other authors. The chosen method allows obtaining an accurate match between the theoretical expressions and experimental results.